Critical role of device geometry for the phase diagram of twisted bilayer graphene - Goodwin,Z; Vitale,V; Corsetti,F; Efetov,DK; Mostofi,AA; Lischner,J (Physical Review B: Condensed Matter and Materials Physics, 2020)
The effective interaction between electrons in two-dimensional materials can be modified by their environment, enabling control of electronic correlations and phases. Here, we study the dependence of electronic correlations in twisted bilayer graphene (tBLG) on the separation to the metallic gate(s) in two device configurations. Using an atomistic tight-binding model, we determine the Hubbard parameters of the flat bands as a function of gate separation, taking into account the screening from the metallic gate(s), the dielectric spacer layers, and the tBLG itself. We determine the critical gate separation at which the Hubbard parameters become smaller than the critical value required for a transition from a correlated insulator state to a (semi)metallic phase. We show how this critical gate separation depends on twist angle, doping, and the device configuration. These calculations may help rationalize the reported differences between recent measurements of tBLG's phase diagram and suggest that correlated insulator states can be screened out in devices with thin dielectric layers.